REAL MATHEMATICS EDUCATION (RME) UNTUK MENINGKATKAN HASIL BELAJAR DAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA SEKOLAH DASAR - Mukti Sintawati; Lina Berliana; Sigit Supriyanto (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2020)
The low ability of students in the field of mathematics based on the results of the Trend In International Mathematics And Science Study (TIMSS) research has become an evaluation for governments and teachers in the process of learning mathematics. Abstract mathematical learning concepts are one of the causes of students' difficulty in understanding mathematics. Therefore, in teaching mathematics, teachers must provide a bridge so that mathematics looks more concrete for elementary school students. Real Mathematics Education (RME) is one approach that teachers can use in learning mathematics. RME is an approach to learning mathematics that uses the context of everyday life to introduce mathematics. The context of everyday life is a concrete bridge to introduce abstract mathematical concepts. The purpose of this study is to apply RME in mathematics learning to improve problem-solving abilities and mathematics learning outcomes of 5th-grade students at Muhammadiyah Argosari Elementary School. This type of research is classroom action research. The implementation of this research consisted of two cycles. The results of this study indicate that RME can be used as alternative learning to improve problem-solving abilities and student learning outcomes.